A farsa que se repete: ataque ao “marxismo cultural” e à educação crítica no Governo Bolsonaro - Carlos Soares Barbosa (Confluenze, 2021)
In this text I seek to identify the implicit interests of the attacks on the supposed "cultural Marxism", which according to the Bolsonaro’s government predominates in the Brazilian public education. Using the method of historical-dialectical materialism, I conclude that the intention of these attacks is to legitimize the interruption of recent social advances, ensure the appropriate conditions for capitalism and institute uncritical training for the working class, in order to prevent questions and social manifestations that would address the worsening of the social inequality, thus maintaining brazilians dependent of capitalism.